2021
DOI: 10.3389/fcell.2020.585565
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0004277 Stimulates Malignant Phenotype of Hepatocellular Carcinoma and Epithelial-Mesenchymal Transition of Peripheral Cells

Abstract: Accumulating evidence shows that exosomal circRNAs reflect the physiological status of donor cells, and various cell reactions are induced after exosomal circRNAs are captured by recipient cells. In this study, qRT-PCR was performed to detect circ-0004277 expression in hepatocellular carcinoma (HCC) cell lines, tissues, and plasma exosomes. The effects of circ-0004277 on the proliferation and migration of HCC cells were assessed by cell counting, 5-ethynyl-2′-deoxyuridine assays, Transwell migration assays, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 48 publications
0
44
0
Order By: Relevance
“…circ_0004277 was significantly upregulated in HCC cells, tissues and plasma exosomes. Exosomal circ_0004277 from HCC cells enhanced the circ_0004277 expression in surrounding normal cells through cellular communication, thus stimulating EMT process and promoting the invasion of HCC cells 160 . In addition, the expression of exosomal circZNF652 was upregulated in the serum of HCC patients and was closely associated with the proliferation, migration, invasion and glycolysis of HCC cells, suggesting that it might become a novel biomarker for predicting the malignant characteristics of HCC 161 .…”
Section: M6a Modifiers and Circrnas As Biomarkers And Therapeutic Targets For Hccmentioning
confidence: 98%
“…circ_0004277 was significantly upregulated in HCC cells, tissues and plasma exosomes. Exosomal circ_0004277 from HCC cells enhanced the circ_0004277 expression in surrounding normal cells through cellular communication, thus stimulating EMT process and promoting the invasion of HCC cells 160 . In addition, the expression of exosomal circZNF652 was upregulated in the serum of HCC patients and was closely associated with the proliferation, migration, invasion and glycolysis of HCC cells, suggesting that it might become a novel biomarker for predicting the malignant characteristics of HCC 161 .…”
Section: M6a Modifiers and Circrnas As Biomarkers And Therapeutic Targets For Hccmentioning
confidence: 98%
“…The increased expression of exosomal circ-0004277 in HCC presents good diagnostic value because its area under the curve (AUC), sensitivity, and specificity are 0.816, 58.3% and 96.7%, respectively. Those results demonstrated that exosomal circ-0004277 might be a useful diagnostic biomarker and therapeutic target for HCC patients (129).…”
Section: Circrnas As Diagnostic and Prognostic Biomarkers For Hccmentioning
confidence: 90%
“…236 Exosomal circ-0004277 plays a role in inducing malignant phenotype of HCC by suppressing expression of ZO-1 and increasing tumor cell progression, migration, and EMT. 237 In addition, the level of serum exosomal CircPTGR1 is upregulated in HCC patients and plays a role in facilitating tumor metastasis by targeting miR449a/MET pathway. 238 Overexpression of exosomal has-circ-0039411 increases secretion of matrix metallopeptidase 2 (MMP2) by sponging miR-136-5p.…”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%